Analysis Numerical Of Torsion Strength Of Low Carbon Steel Using Software (Solidworks) - Affandi; Syifaul Huzni (Universitas Muhammadiyah Sidoarjo, 2021)
One of the components, namely the shaft that is subjected to torsion will experience torsional deformation. The greater the torsional deformation indicates the ability of the engine components is low, and vice versa. The problem that often occurs during torsional testing is that processing the data into a shear stress-strain curve requires a lot of effort. If the specimen used is a solid rod, there will be a fairly steep stress gradient along the cross-section of the specimen making measurements difficult. The objective of this research is to identify and analyze the torsional strength test on low carbon steel by a numerical method using SolidWorks software. The torsion test specimen is low carbon steel with ASTM E-143 standard. This research method begins with a literature study, testing the composition of the test specimen, making and modeling torsion test specimens. After that, torsional testing was carried out which was then carried out with static simulation tests. Then perform a torsional strength analysis using the finite element method using software (SolidWorks). Based on the results of geometry making and modeling of torsion test specimens with ASTM E-143 standard, that the stress distribution that occurs on the surface of the specimen angle area has a value that is not too significant, ranging from 2.879e+09 and 2.973e+09. However, it is necessary to simulate the torsion test of the SolidWorks software with varying mesh sizes and torsion test specimens with different ASTM standards.